Instructional quality in nursing vocational education and training - Anselmann, Veronika; Roggenstein, Jennifer; Thudium, Leonie (Frontiers in Education, 2025)
IntroductionInstructional quality refers to classroom management, personal learning support and cognitive activation.MethodsThis study was conducted in nurses’ vocational education and training (VET). We asked nursing students (N = 496) to estimate instructional quality of their classes (n = 52). Furthermore, we asked teachers (N = 52) to describe the learning objectives they aimed to achieve. We used online and paper- pencil questionnaires with validated scales to measure classroom management, personal learning support, and cognitive activation, and connectivity. For analyzing our data, we used descriptive statistics and Anova with Bonferroni and Turkey’ post hoc tests. We also used structuring qualitative content analysis to teachers’ descriptions of learning goals.ResultsOur results indicate that nursing students estimated the instructional quality of their classes quite high. When teacher aimed on achieving higher levels of learning objectives classroom management and personal learning support were estimated significantly different.DiscussionIn VET it is important to coordinate the content, the way of instruction, and the way learners are supported in the learning process to achieve high instructional quality.